Case Report: Emergency High-Risk Percutaneous Coronary Intervention Following Transcatheter Aortic Valve Implantation in Bicuspid Anatomy - El-Medany, Ahmed; Doolub, Gemina; Dastidar, Amardeep; Joshi, Nikhil; Johnson, Thomas; Dorman, Stephen (Frontiers in Cardiovascular Medicine, 2021)
Background Transcatheter aortic valve implantation (TAVR) continues to develop as a valuable alternative to surgical aortic valve replacement (SAVR) in an increasingly wide spectrum of patients with severe symptomatic aortic stenosis (AS). AS frequently coexists with coronary artery disease and performing technically challenging percutaneous coronary intervention (PCI) following TAVR will become more frequent with increased use of TAVR. Case summary We herein report the case of a 53-year-old man with complex medical history including type 1 diabetes and dialysis dependent renal failure, and prior Evolut-R TAVR for critical bicuspid aortic valve stenosis, who underwent intravascular ultrasound study (IVUS) guided PCI to a critical distal left main stem (LMS) and proximal left anterior descending (LAD) lesion after presenting with ventricular fibrillation (VF) secondary to an acute coronary syndrome (ACS). Discussion Selective engagement of coronary ostia through the side cells of TAVR prosthesis can be challenging, especially in an emergency setting. The particular challenges associated with this case are described, as well as an up-to-date literature search on strategies and equipment that can help in this situation.